PENGARUH LATIHAN TERHADAP PENINGKATAN KEMAMPUAN BERMAIN BOLA VOLI - Rahmi Aulia; Muhammad Rizqi Pahlan Siregar; Febrian Mael Pratama Purba; Rashya Sahbana Ansaric Nasution; Yudha Panjaitan (STKIP Subang, 2026)
This study aims to analyze the effect of training on improving volleyball playing skills. The research method used is a qualitative approach with a library research design, collecting data from various sources such as scientific journals, books, and relevant articles. Data collection was conducted through documentation techniques, while data analysis used a descriptive comparative method by comparing results from previous studies. The results show that training has a significant effect on improving volleyball playing skills, especially basic techniques such as overhead passing and underhand passing. Various training methods such as drills, paired exercises, and wall training have proven effective in improving players' skills. In addition, structured and continuous training provides more optimal results. Therefore, it can be concluded that training is an important factor in improving volleyball playing abilities.